Factors influencing the motivation to participate in volunteer activities among students of Tan Trao University - Nguyen, Tran Thao; Dao, Hoang Anh (International Journal of Scientific Research and Management (IJSRM), 2025)
In the context of volunteer activities playing an increasingly important role in developing skills and social responsibility among university students, this study developed a model consisting of five independent factors, including: personal intrinsic motivation, influence from others, institutional encouragement, skill development, and achievements and career opportunities—which influence the motivation to participate in volunteer activities among students at Tan Trao University. A mixed-methods research approach was applied, based on data collected from 1,075 students. Analyses were conducted using SPSS 26.0, including Cronbach’s Alpha reliability testing, Exploratory Factor Analysis (EFA), Pearson correlation, and linear regression. The results show that all five factors have a positive and statistically significant impact on students’ decisions to engage in volunteer activities. Among them, skill development was identified as the most influential factor. Based on these findings, the study proposes a number of solutions for universities to better attract and encourage student participation in volunteer programs—not only to foster their personal growth but also to promote positive contributions to the community.